Deletion of TAK1 in the myeloid lineage results in the spontaneous development of myelomonocytic leukemia in mice - Lamothe,B; Lai,Y; Hur,L; Orozco,NM; Wang,J; Campos,AD; Xie,M; Schneider,MD; Lockworth,CR; Jakacky,J; Tran,D; Ho,M; et al. (PLoS One, 2012)
Previous studies of the conditional ablation of TGF-β activated kinase 1 (TAK1) in mice indicate that TAK1 has an obligatory role in the survival and/or development of hematopoietic stem cells, B cells, T cells, hepatocytes, intestinal epithelial cells, keratinocytes, and various tissues, primarily because of these cells’ increased apoptotic sensitivity, and have implicated TAK1 as a critical regulator of the NF-κB and stress kinase pathways and thus a key intermediary in cellular survival. Contrary to this understanding of TAK1’s role, we report a mouse model in which TAK1 deletion in the myeloid compartment that evoked a clonal myelomonocytic cell expansion, splenomegaly, multi-organ infiltration, genomic instability, and aggressive, fatal myelomonocytic leukemia. Unlike in previous reports, simultaneous deletion of TNF receptor 1 (TNFR1) failed to rescue this severe phenotype. We found that the features of the disease in our mouse model resemble those of human chronic myelomonocytic leukemia (CMML) in its transformation to acute myeloid leukemia (AML). Consequently, we found TAK1 deletion in 13 of 30 AML patients (43%), thus providing direct genetic evidence of TAK1’s role in leukemogenesis.